Être vu au spectacle de la religion pour témoigner de ses croyances religieuses ? - Alexandre Jakubiec (Pallas, 2018)
The religious beliefs of the Greeks are quite neglected in historiography, contrary to the rites. Nevertheless, sources of the classical period, of which some deserve a new interpretation, show that some Greeks, in particular in Athens, could be concerned with the religious beliefs of others and, to know them, observe their religious practices. Similarly, some could feel the obligation to be seen at the show of religion to avoid giving arguments to possible charges of disbelief.